Love's enduring promise eaudiobook Love comes softly series, book 2. - Oke, Janette (Love Comes Softly, 2015)
Tragedy Brought Them Together, But Love Bound Them Into a Family Love Comes Softly, a novel made into a Hallmark Channel Original Movie by Michael Landon Jr., has introduced millions of readers to Clark and Marty Davis, caught in a marriage of convenience that over time turned into deep mutual respect and love. In this sequel, they now preside over a growing family in their little prairie house. But as they reach out to those in their frontier community, they discover that love is not limited by the size of a dwelling. Winner of the Gold Book Award